The AbcA Transporter of Staphylococcus aureus Affects Cell Autolysis - Schrader-Fischer, Gesine (American Society for Microbiology, 2001)
Increased production of penicillin-binding protein PBP 4 is known to increase peptidoglycan cross-linking and contributes to methicillin resistance in Staphylococcus aureus. The pbp4 gene shares a 400-nucleotide intercistronic region with the divergently transcribed abcA gene, encoding an ATP-binding cassette transporter of unknown function. Our study revealed that methicillin stimulated abcA transcription but had no effects on pbp4 transcription. Analysis of abcA expression in mutants defective for global regulators showed that abcA is under the control of agr. Insertional inactivation of abcA by an erythromycin resistance determinant did not influence pbp4 transcription, nor did it alter resistance to methicillin and other cell wall-directed antibiotics. However, abcA mutants showed spontaneous partial lysis on plates containing subinhibitory concentrations of methicillin due to increased spontaneous autolysis. Since the autolytic zymograms of cell extracts were identical in mutants and parental strains, we postulate an indirect role of AbcA in control of autolytic activities and in protection of the cells against methicillin.